Current Scenario Of Revenue Structure Of Indian Media: An Overview (International Journal of Food and Nutritional Sciences, 2022)
The Indian media and entertainment (M & E) industries are unique in the world, as is the Indian film industry. As India's media business has seen dramatic and transformational change over the past two decades, as evidenced by the increase of both channels and audiences. It has a massive income structure, which is aided by technological advancements and the internet. As per ongoing evaluations, the nation has in excess of 100 news channels that reach 161 million families, around 94,067 papers, and in excess of 200 million Internet clients. According to ongoing evaluations, the country is home to more than 100 news channels that reach over 161 million families, around 94,067 newspapers, and more than 200 million Internet users, in addition to other things. Following these changes, a new body of discourse has emerged that highlights the expansion and vitality of the Indian media. As a result, the purpose of this study is to analyse the revenue structure present and forecast for the past several years.